Can Magnetic Resonance-Ultrasound Fusion Biopsy Improve Cancer Detection in Enlarged Prostates? - Diaz, Annerleim Walton (J Urol, 2013)
PURPOSE: Patients with an enlarged prostate and suspicion of prostate cancer pose a diagnostic dilemma. The prostate cancer detection rate of systematic 12-core transrectal ultrasound guided biopsy is between 30% and 40%. For prostates greater than 40 cc this decreases to 30% or less. Magnetic resonance-ultrasound fusion biopsy has shown superior prostate cancer detection rates. We defined the detection rate of magnetic resonance-ultrasound fusion biopsy in men with an enlarged prostate gland. MATERIALS AND METHODS: We retrospectively analyzed the records of patients who underwent multiparametric prostate magnetic resonance imaging followed by magnetic resonance-ultrasound fusion biopsy at our institution. Whole prostate volumes were calculated using magnetic resonance imaging reconstructions. Detection rates were analyzed with respect to age, prostate specific antigen and whole prostate volumes. Multivariable logistic regression was used to assess these parameters as independent predictors of prostate cancer detection. RESULTS: We analyzed 649 patients with a mean ± SD age of 61.8 ± 7.9 years and a median prostate specific antigen of 6.65 ng/ml (IQR 4.35–11.0). Mean whole prostate volume was 58.7 ± 34.3 cc. The overall detection rate of the magnetic resonance-ultrasound fusion platform was 55%. For prostates less than 40 cc the detection rate was 71.1% compared to 57.5%, 46.9%, 46.9% 33.3%, 36.4% and 30.4% for glands 40 to 54.9, 55 to 69.9, 70 to 84.9, 85 to 99.9, 100 to 114.9 and 115 cc or greater, respectively (p <0.0001). Multivariable logistic regression showed a significant inverse association of magnetic resonance imaging volume with prostate cancer detection, controlling for age and prostate specific antigen. CONCLUSIONS: Transrectal ultrasound guided and fusion biopsy cancer detection rates decreased with increasing prostate volume. However, magnetic resonance-ultrasound fusion biopsy had a higher prostate cancer detection rate compared to that of transrectal ultrasound guided biopsy in the literature. Magnetic resonance-ultrasound fusion biopsy represents a promising solution for patients with suspicion of prostate cancer and an enlarged prostate.